Omega Fatty Acids In Health And Diseased State - A Review - M, NIVEDHA; GEETHA, R.V.; DON, K.R. (The journal of contemporary issues in business and government, 2020)
The dietary lipids have a significant job in tweaking the onset of autoimmunity, cardiovascular diseases and cancer. Several studies have been led to build up the adverse impacts of saturated fats in humans and animals. The intake of oils containing both monounsaturated omega-9 and polyunsaturated fats in essentially emerging over certain nations. Yet, the increased uptake of certain vegetable oils of ω-6 series is anyway to be seen as proinflammatory and it is one of the potential causes for the steady ascent in some malignant tumors, rheumatoid arthritis and autoimmune disease that are basically caused because of the increased production of proinflammatory cytokines. Diets dependent on ω-6 enhanced oils can elevate the level of linolenic acid in tissue phosphoglycerides and can lessen cholesterol levels. Yet these lipids tend to increase unnecessary rise of arachidonic acids. In contrast, ω-3 fatty acids-enriched fish oils or omega-3 precursors from certain vegetable oils are found to give protection against cardiovascular disease, rheumatoid arthritis, cancer and against the seriousness of some viral diseases.